2013
DOI: 10.1103/physrevb.87.235119
|View full text |Cite
|
Sign up to set email alerts
|

Edge states in horseshoe-shape carbon nanotubes transformed by hydrogen adsorption

Abstract: We have investigated hydrogenated single-wall armchair (n,n) carbon nanotubes (CNTs) with 4 n 12 by using density functional theory calculations. Hydrogen adsorption may transform the CNTs into a horseshoe shape. Nonmagnetic edge-localized electron states have been identified in CNTs of horseshoe shape in this work. The σ -bond-like orbital overlaps across the edge-localized electrons, which sustain the horseshoe shape of the CNTs and hinder spontaneous unravelling into a graphene nanoribbon, cause the horsesh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2014
2014
2016
2016

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…This proposal is supported by several magnetic penetration depth measurements on this family of superconductors, which all argued that the BiS 2 -based superconductors are the conventional s-wave type superconductors with fully developed gaps [14][15][16] . However, a recent neutron scattering work suggested that the e-ph coupling in LaO 0.5 F 0.5 BiS 2 could be much weaker than expected 17 . Band calculations found that the Fermi surface of LaO 0.5 F 0.5 BiS 2 is quasi-one-dimensional, which would provide a good nesting condition.…”
Section: Introductionmentioning
confidence: 75%
“…This proposal is supported by several magnetic penetration depth measurements on this family of superconductors, which all argued that the BiS 2 -based superconductors are the conventional s-wave type superconductors with fully developed gaps [14][15][16] . However, a recent neutron scattering work suggested that the e-ph coupling in LaO 0.5 F 0.5 BiS 2 could be much weaker than expected 17 . Band calculations found that the Fermi surface of LaO 0.5 F 0.5 BiS 2 is quasi-one-dimensional, which would provide a good nesting condition.…”
Section: Introductionmentioning
confidence: 75%
“…The nominal centrosymmetric structure P4/nmm (T 0 ) structure, which has equal Bi-S 1 bonds in x-y plane, was used in X-ray refinement of the crystal structure of the prototype material LaBiOS 2 first in 1995 22 , and in many other following experiments [23][24][25] . However, recently it was shown theoretically that phonon instability will make the two in-plane Bi-S 1 bonds in the assumed P4/nmm structure LaOBiS 2 non equivalent 26 so as to remove the instability.…”
Section: A Crystal Structurementioning
confidence: 99%
“…As shown in Fig. 4(a) by the asterisks, DE of (n,n)CNT-H0z is at best 10 meV, as is the case for (8,8)CNT-HNz for N 3, and gradually decreases with increasing n. (n,n)CNT-H(2nÀ1)z, which is expected to have the BE part only, is known to be transformed into a horseshoe shape of a nonmagnetic metal [16,17] and thus DE for the BE part only was not obtained. Instead, DE was investigated for a fixed width of the BE part and for a fixed width of the ZE part as a function of the width of the opposite part, only the contribution from the part with a fixed width being expected to survive at large widths of the opposite part.…”
Section: Resultsmentioning
confidence: 91%
“…The BE part enlarges with N, reducing the ZE part, and only bearded edges will remain when N ¼ (2nÀ1). However, in practice, (n,n) CNT-H(2nÀ1)z, in which hydrogen atoms are adsorbed on the CeC pairs perpendicular to the tube axis, is known to be transformed into a horseshoe-shape of nonmagnetic metal [16,17], which is out of the scope of this work.…”
Section: Introductionmentioning
confidence: 98%